PENGARUH PENAMBAHAN TEPUNG GAPLEK DENGAN LEVEL YANG BERBEDA TERHADAP KADAR BAHAN KERING DAN KADAR BAHAN ORGANIK SILASE LIMBAH SAYURAN - Devi Desnita; Yusuf Widodo; Syahrio Tantalo YS (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Vegetable waste in the trditional market can be used as feed. Nevertheless, the shortcomings from vegetable waste is have a high level of water content. Vegetables waste can be processed to be silage with addition accelerators that is cassava flour. This research determined to: 1) the effect of the addition cassava flour with different levels on the levels of dry substances and levels of organic matters in vegetable waste silage; 2 ) the best increasing rate of cassava flour against to dry subtances and organic matters in vegetables waste silage. The design used Completely Random Design (CRD) with five treatments additonal cassava flour (0%, 5%, 10%, 15% and 20%) and each treatments was repeated for three times and the data was analyzed with Least Significant Difference test (LSD). The result indicated that additonal levels of cassava flour was highly significant ;(P<0,01) on the levels of dry substances and levels of organic matters vegetables waste. Best treatment is in vegetable waste silage that added 20 % cassava flour against to dry substances levels and levels of organic matter. Keywords: Vegetable waste silage, Cassava flour, Dry substances, and Organic matter).